Issledovanie chronobiologiceskich osobennostej vospitanija vremeni i prostranstva u sportsmenov - Korjagina, Ju. V. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The purpose of the research was the studying of chronobiological features of the accuracy of the perception of time and space by the athletes specializing in various kinds of sports and having a different level of motor activity. 910 persons have taken part in the research: the athletes specializing in various kinds of sports (579), the persons engaged in physical culture (133), and not engaged in sports (198). The research of the accuracy of perception of time and space was carried out with the help of specially developed technique, which included the tasks on estimating and measurement of time and spatial intervals.